Burundi : Fifth Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for Extension of the Arrangement; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2011)
Burundi is one of the poorest countries in the world. The country is emerging from more than a decade of civil conflict. The World Bank's country assistance strategy focuses on structural reforms to further increase growth and reduce poverty. The economy is emerging from the effects of the global crisis. Performance under the Extended Credit Facility-supported (ECF) program has been satisfactory. The discussions focus on the appropriate policy mix to consolidate economic stability and support recovery of the economy. The economy is expected to continue to recover from the effects of the global crisis.